PENERAPAN ALGORITMA APRIORI PADA SISTEM REKOMENDASI BARANG DI MINIMARKET BATOX - Nur Fitrina; Kustanto Kustanto; Retno Tri Vulandari (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2018)
Recommendations are application models from previous measurement of data and information. To process data that is quite a lot is used the right method. Association rules are one technique that can be used in associating indirect data from a data. The purpose of this study is to create a system that can be used to provide information on goods in accordance with consumer combinations. The method used is direct interviews with staff to get information in the form of sales data and system requirements. The design model uses the System Development Life Cycle (SDLC), namely Analysis, Design, Construction, Implementation, and Testing. The system design method used is UML (Unified Modeling Language). The system used is an algorithm that is made web-based using the language PHP and MySQL as databases. The results used in this study are to stop at the specified 2-item iteration and two rules that meet minimum 30% support rules and a minimum confidence of 70%, namely Cofemix → Sugar and Sugar → Sugar.